All about light and sound - Jankowski, Connie (Compass Point Books, 2010)
Explains why light and sound are vital in observing the world, and describes how light is made; reflection, refraction, and absorption; how the eye and ears work; the Doppler effect; and the speed of sound; and includes instructions for a simple periscope.